2010
DOI: 10.1038/gt.2010.102
|View full text |Cite
|
Sign up to set email alerts
|

Clearance and characterization of residual HSV DNA in recombinant adeno-associated virus produced by an HSV complementation system

Abstract: Encapsidation of cellular-or plasmid-derived DNA sequences during recombinant adeno-associated virus (rAAV) production has been well documented. However, most of the published data were generated from rAAV vectors manufactured by the plasmid transient transfection method. We previously reported a novel, scalable method for rAAV manufacturing based on a recombinant herpes simplex virus (rHSV) complementation system. In this report, we evaluated clearance of DNA impurities during rAAV purification, by determinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 26 publications
0
25
0
2
Order By: Relevance
“…With many clinical trials under way, assessing the genetic identity of rAAV stocks manufactured by different protocols becomes a pressing regulatory issue. Many groups have reported a collateral encapsidation of sequences derived from packaging host cells, 25,30,31 bacterial helper plasmid backbones, 25,32 helper viruses, 8,31 and wild-type (WT) AAV rep/cap sequences. 25,33 To evaluate the genetic identity of the packaged rAAV cassette, we set to conduct NGS analysis of encapsidated single-stranded viral DNA.…”
Section: Discussionmentioning
confidence: 99%
“…With many clinical trials under way, assessing the genetic identity of rAAV stocks manufactured by different protocols becomes a pressing regulatory issue. Many groups have reported a collateral encapsidation of sequences derived from packaging host cells, 25,30,31 bacterial helper plasmid backbones, 25,32 helper viruses, 8,31 and wild-type (WT) AAV rep/cap sequences. 25,33 To evaluate the genetic identity of the packaged rAAV cassette, we set to conduct NGS analysis of encapsidated single-stranded viral DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported a range of common DNA contaminants in rAAV preparations, including plasmid backbone sequences such as antibiotic resistance markers or elements from the capsid and helper packaging plasmids, and genomic DNA from the packaging cells. [2][3][4][5][6][7][8][9][10][11] Although the effect of contaminating DNA on downstream applications remains unclear, it has been demonstrated that it can persist in mammalian systems for months after the vector has been administered. 3 Previous work using single molecule real-time sequencing (SMRT), ligation of thymine and adenine overhangs (TA-based ligation), and tagmentation-based library preparation methods have proved that NGS is an effective tool to confirm rAAV genome sequence and identify vector preparation anomalies such as truncated genomes, reverse packaging, and the presence of contaminating DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Separation of full and empty capsids was performed as previously described. 19 Briefly, an aliquot of purified Master rAAV2tYF-CMV-hGFP (4.2 • 10 13 vg) made by rHSV helper viruses was supplemented with CsCl to a final density of 1.40 gcm -3 , loaded into a Beckman ultracentrifuge tube and subjected to ultracentrifugation at 60,000 r.p.m. for 20 h in a 70Ti rotor.…”
Section: ''Enriched Full'' and ''Enriched Empty'' Vectormentioning
confidence: 99%